A Dithiol Compound Binds to the Zinc Finger Protein TRAF6 and Suppresses Its Ubiquitination. (4th October 2017) - Koga, Ryoko; Radwan, Mohamed O.; Ejima, Tomohiko; Kanemaru, Yosuke; Tateishi, Hiroshi; Ali, Taha F. S.; Ciftci, Halil Ibrahim; Shibata, Yuri; Taguchi, Yuu; Inoue, Jun‐ichiro; Otsuka, Masami; Fujita, Mikako
Abstract: Despite various inhibitors targeting the zinc center(s) of enzymes, drugs that target zinc fingers have not been examined in detail. We previously developed a dithiol compound named SN‐1 that has an inhibitory effect on the function of zinc finger transcription factors, but its mechanism of action has not yet been elucidated. To establish a general principle for new drugs, the details of the action of SN‐1 against a zinc finger protein were examined. As a zinc‐finger‐containing protein, we focused on TRAF6, which is related to cancer and inflammation. Binding of SN‐1 to TRAF6 and its effect on TRAF6 ubiquitination were examined in vitro, and the binding mode was calculated by computational methodology. Furthermore, ubiquitination of TRAF6 and downstream signaling was examined by cell‐based experiments. The results show that SN‐1 binds to TRAF6, inhibiting its auto‐ubiquitination and downstream NF‐κB signaling. Docking studies indicate that SN‐1 binds directly to the first zinc finger of TRAF6. This binding disrupts the neighboring structure, that is, the RING finger domain, to suppress the ubiquitin ligase activity of TRAF6. Taken together, this study provides a platform for developing new small molecules that target zinc finger proteins. Abstract : A dithiol compound named SN‐1 binds to TRAF6, inhibiting its auto‐ubiquitination and downstream signaling. SN‐1 is considered to bind directly to the first zinc finger of TRAF6, disrupting the neighboring RING finger domain, to suppress the ubiquitin ligase activity of TRAF6. This study provides a platform for developing new small molecules that target zinc finger proteins.